PREFERENCES OF USING QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) AMONG STUDENTS AS A MEANS OF DIGITAL PAYMENT - Yudistira Andi Permadi; Angestika Wilandari (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2021)
QRIS is a digital payment instrument that has provided positive signals since it was launched. It is known that the demographics of QRIS users are quite diverse, including students. This study aims to determine students' preferences in Jabodetabek in using QRIS as a means of digital payment. Preference or interest in using QRIS that arises in this study is measured using the following four characteristics: 1) Easiness Characteristic; 2)Usefulness Characteristic; 3) Risk Characteristic, and 4) Trust Characteristic. The research results by distributing questionnaires conducted showed that of 154 respondents, the majority felt the easiness and benefits of the QRIS. However, even though it is easy and useful, respondents are still cautious and show a lack of trust in using QRIS because it is considered quite risky.